Effects of emergent vegetation on open channel flow - Zhang, Linyue (2010)
The presence of vegetation in an open channel has significant influences on hydrodynamic characteristics such as velocity distribution, flow discharge and turbulence structures, making the situation become much more complex than usual cases. Experiments and studies were carried out in CEE Hydraulics Lab, NTU, to explore the effect of emergent vegetation on open channel flow. In the flume experiments, two kinds of vegetation models were tested in the condition of uniform flow with five different flume bed slopes. Electromagnetic Current Meter (EMCM) was used to measure the flow velocity at a specific location. By analyzing four main parameters, velocity distribution, flow discharge, Manning’s roughness coefficient and turbulence structure, the effects of emergent vegetation on uniform open channel flow are identified.